Lógica intuicionista dual y álgebras de Co-Heyting (2009)
Presentamos ejemplos de álgebras de Heyting, co-Heyting y bi-Heyting y relaciones con las lógicas intuicionista, dual-intuicionista y bi-intuicionista. Estudiamos los operadores modales descritos en Reyes and Zolfaghari, 1996. Finalmente, indicamos una extensión de los teoremas de representación para álgebras de Heyting, Co-Heyting y bi-Heyting de Esakia mediante los espacios bi-topológicos introducidos en Bezhanishvili, et al. 2010. / Abstract. We present examples of Heyting, co-Heyting and bi-Heyting algebras and relations with intuitionism, dual-intuitionism and bi-intuitionism logics. We study the modal operators described in Reyes and Zolfaghari, 1996. Finally, we comment the extension of Esakia’s representation theorems for Heyting, co-Heyting and bi-Heyting algebras by means of bi-topological spaces in Bezhanishvili, et al. 2010.